Spectrum-efficient real-time OFDM MIMO Radar for moving target detection in medium-range applications - Multerer, Thomas; Vossiek, Martin; Prechtel, Ulrich; Ziegler, Volker (IEEE MTT-S International Conference on Microwaves for Intelligent Mobility (ICMIM 2018), 2018)
This paper presents the first measurement results of a new Orthogonal Frequency Division Multiplexing (OFDM) Multiple Input Multiple Output (MIMO) Radar prototype. It is designed to be operated in a dynamic multi-user environment where the individual sensor's RF bandwidth is very limited. Here, the radar uses only 30 MHz. The targeted applications are in the field of Urban (Air) Mobility (UAM) with a medium-range coverage up to 250 m. Another requirement is to observe a wide field of view in azimuth of about 100 degree with a high resolution in azimuth. This was implemented by using a 2 × 8 MIMO processing. A 20 ms frame based evaluation of the OFDM symbols allows to obtain a very high velocity resolution of below 1 m/s. This paper explains details about the radar system, the waveform and the processing but the main part of the paper focuses on the evaluation of a dynamic measuremen
lhft_intern.bib::Multerer2018a

Systematic Phase Correction for Direction-of-Arrival Estimation in Spectrally Interleaved OFDM MIMO Radar - Multerer, Thomas; Prechtel, U; Vossiek, Martin; Ziegler, Volker (IEEE Transactions on Microwave Theory and Techniques, 2019)
This paper presents a phase correction methodto improve direction-of-arrival (DOA) estimation in spectrallyinterleaved orthogonal frequency-division multiplexing (OFDM)multiple-input-multiple-output (MIMO) radar systems. It is newin the way that a phase correction step is introduced betweenthe range-Doppler processing and the DOA estimation. Thephase correction results in an improved dynamic range. Bothprocessing steps, range–velocity and DOA, are performed usingdiscrete Fourier transforms (DFTs). This paper starts by intro-ducing the waveform and reviewing range–velocity processing inOFDM radars. After that, the new phase correction method isintroduced. Then, the concept is implemented in a quantitativesimulation. The last part includes the system description andmeasurement in an outdoor scenario. Finally, the simulation andmeasurement results are discusse